Evaluation of the ‘H2NOE Water Schools’ programme to promote water consumption in elementary schoolchildren: a non-randomised controlled cluster trial - Griebler, Ursula; Titscher, Viktoria; Weber, Michael; Affengruber, Lisa (Public health nutrition, 2022)
This study evaluated a simple environmental intervention called 'Water Schools' in Lower Austria providing free refillable water bottles and educational material. Non-randomised controlled cluster trial with three measurements: at baseline (T0), after the intervention at 9 months (T1) and after 1-year follow-up (T2). Half-day elementary schools in Lower Austria (Austria). Third-grade pupils from twenty-two schools in the intervention group (IG) and thirty-two schools in the control group (CG) participated in the study. Data were analysed for 569 to 598 pupils in the IG and for 545 to 613 in the CG, depending on the time of measurement. The consumption of tap water increased in the IG from baseline to T1 and then decreased again at T2, but this was similar in the CG (no statistically significant difference in the time trend between the IG and CG). Similar results were seen for tap water consumption in the mornings. The proportion of children who only drank tap water on school mornings increased significantly from baseline to T1 in the IG compared to the CG (P = 0·020). No difference in the changes over time occurred between the groups for the proportion of pupils drinking approximately one bottle of tap water during school mornings. Not only the children in the IG but also those in the CG drank more tap water after 1 school year than at the beginning. The measurement of drinking habits in the CG may have been intervention enough to bring about changes or to initiate projects.